Risk factors for infant formula usage during the initial hospital stay in term and late pre-term neonates after implementation of a breastfeeding support program: A retrospective case–control study from a tertiary care hospital - Ganapathy, Suja Mariam; Buddhavarapu, Siddartha (Indian Journal of Child Health, 2024)
Background: Infant formula usage in hospitals is inevitable in certain circumstances. We explored the high-risk groups who required formula during hospital stays during the post-intervention phase of a quality improvement initiative for improving exclusive breastfeeding (EBF) rates in hospitals. Methods: A retrospective and case–control study was conducted involving 50 cases of neonates who received infant formula and 200 control who were exclusively breastfed. Data regarding maternal and neonatal details were from breastfeeding assessment forms and case record which was collected prospectively during the program. We compared common risk factors between the two groups. Results: There was a strong association between infant formula usage and cesarean sections, assisted reproductive technology (ART) conceptions, multiple gestations, neonatal intensive care unit admissions, being small for gestational age, and being an infant of a diabetic mother. First-h breastfeeding was associated with a higher likelihood of EBF in the hospital. In the final model, ART conception, multiple gestations, and delayed initiation of breastfeeding were strong predictors of the use of infant formula in the hospital. Conclusion: Initiating breastfeeding within the 1st h promotes EBF. ART conception and multiple gestations remain strong risk factors for formula usage, the social, physiological, and genetic reasons for which will need to be studied in detail.